Knowledge of Shahid Beheshti Dental School Faculty Members about Open Access Electronic Journals - Azin Nourian; Elahe Vahid Dastjerdib; Mohammad Hossein Khoshnevisan (Journal of Dental School, 2019)
Objectives It is important to evaluate the gap of information regarding the online scientific resources available to college and university instructors. The aim of this study was to assess the knowledge of Shahid Beheshti Dental School faculty members about open access electronic journals. Methods A questionnaire was used to collect information on 68 available faculty members of the Shahid Beheshti Dental School in this descriptive, cross-sectional study. Among others, the questionnaire asked for demographic information, academic level and current status of using electronic journals. The validity and reliability of the questionnaire were assessed using Cronbach’s alpha and content validity statistics. The collected data were analyzed using SPSS software. The descriptive statistics such as percentage, mean and standard deviation and non-parametric tests such as binomial, Friedman, Kruskal Wallis and Mann Whitney tests were used. Results The mean and standard deviation of score on acquaintance with open access electronic journals, the mean score of using these journals and the mean score of attitude of faculty members towards these journals were 3.45 (±0.7), 2.76 (±0.88) and 3.13 (±0.4), respectively. Conclusion The attitude and acquaintance level of the faculty members with open access journals were moderate; while their usage was less than moderate. Therefore, faculty members must be encouraged to use open access journals more frequently in order to keep up with scientific advances in their field.